PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS II SD NEGERI 37 MANDAU - Edriani Umar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by the still low learning outcomes of science students in SD Negeri 37 Mandau. The subjects of this research were grade II students of 37 Mandau Public Elementary Schools, totaling 30 students consisting of 17 male students and 13 female students. This study uses classroom action research consisting of 2 cycles, each cycle through the stages of planning, implementation, observation, and reflection. The results showed that, seen from the initial data of students who completed only 14 students with a percentage of 46.6%. While those who did not complete were 16 students with a percentage of 53.4%. Students who completed the first cycle totaled 22 people with a percentage of 73.3% while students who did not complete experienced a reduction to 8 people with a percentage of 26.7%. Cycle II, students who finished up to 26 people with a percentage of 86.6%, while the number of students who did not complete again decreased to 13.4%. Based on the data obtained above, it can be concluded that applying the picture and picture learning model can improve the learning outcomes of science students in grade II of SD Negeri 37 Pekanbaru